Barreras legales para la producción y comercialización de cannabis medicinal en Colombia (2022)
This project was taken as a background because it proposes a plant for the manufacture of cannabis derivatives in order to change the vision of society about the plant, it also studies the behavior of the cannabis market in Colombia and the world, it also provides the processes and equipment used for the extraction of these derivatives in the industry, as well as the distribution of spaces and equipment in the plant